A Quadruple‐Hydrogen‐Bonded Supramolecular Binder for High‐Performance Silicon Anodes in Lithium‐Ion Batteries. Issue 29 (22nd June 2018) - Zhang, Guangzhao; Yang, Yu; Chen, Yunhua; Huang, Jun; Zhang, Tian; Zeng, Hongbo; Wang, Chaoyang; Liu, Gao; Deng, Yonghong
Abstract: With extremely high specific capacity, silicon has attracted enormous interest as a promising anode material for next‐generation lithium‐ion batteries. However, silicon suffers from a large volume variation during charge/discharge cycles, which leads to the pulverization of the silicon and subsequent separation from the conductive additives, eventually resulting in rapid capacity fading and poor cycle life. Here, it is shown that the utilization of a self‐healable supramolecular polymer, which is facilely synthesized by copolymerization of tert‐butyl acrylate and an ureido‐pyrimidinone monomer followed by hydrolysis, can greatly reduce the side effects caused by the volume variation of silicon particles. The obtained polymer is demonstrated to have an excellent self‐healing ability due to its quadruple‐hydrogen‐bonding dynamic interaction. An electrode using this self‐healing supramolecular polymer as binder exhibits an initial discharge capacity as high as 4194 mAh g −1 and a Coulombic efficiency of 86.4%, and maintains a high capacity of 2638 mAh g −1 after 110 cycles, revealing significant improvement of the electrochemical performance in comparison with that of Si anodes using conventional binders. The supramolecular binder can be further applicable for silicon/carbon anodes and therefore this supramolecular strategy may increase the choice of amendable binders to improve the cycle life and energy density of high‐capacity Li‐ion batteries. Abstract : A quadruple‐hydrogen‐bonded supramolecular polymer that possesses excellent self‐healing properties is designed and applied as a water‐soluble binder in silicon anodes. Silicon electrodes using the self‐healable binder exhibit excellent long‐term cycling stability and superior rate performance, demonstrating that the supramolecular strategy can increase the choice of amendable binders to improve the cycle life of high‐capacity Li‐ion batteries.